Unpacking the Development of Chinese Preservice English as a Foreign Language Teachers’ Professional Knowledge - Liu, Liyan; Jiang, Anne Li; Yang, Shiyu; Li, Shuo (Frontiers in Psychology, 2022)
Efforts to improve preservice teacher education have recently focused on developing teachers’ adequate pedagogical knowledge (PK), content knowledge (CK), and pedagogical content knowledge (PCK), which are critical elements of teachers' professional knowledge, and important indicators of preparedness to teach. However, the development of the three knowledge domains of preservice EFL teachers is surprisingly under-researched. To fill this gap, this study examined the developmental trajectories of the three knowledge domains of a group of Chinese preservice EFL teachers at different stages of a teacher education program. Specifically, it explored the relationship among the three knowledge domains, and the effects of learning opportunities on their development. Findings revealed that preservice EFL teachers at a later stage outperformed those at an earlier stage with regard to PK and PCK. Our findings also suggested that there were positive correlations among PK, CK, and PCK at different stages of the teacher education program. Furthermore, the findings showed that courses on CK, PK and PCK, and teaching experience significantly influenced preservice EFL teachers’ professional knowledge. However, the role of classroom observation was not significant. Implications for EFL teacher education and future research were also discussed.